Recent Progress in the Development of Opaganib for the Treatment of Covid-19 - Smith CD; Maines LW; Keller SN; Katz Ben-Yair V; Fathi R; Plasse TF; Levitt ML (Dove Medical Press, 2022)
Charles D Smith,1 Lynn W Maines,1 Staci N Keller,1 Vered Katz Ben-Yair,2 Reza Fathi,2 Terry F Plasse,2 Mark L Levitt2 1Apogee Biotechnology Corporation, Hummelstown, PA, USA; 2RedHill Biopharma LTD, Tel Aviv, IsraelCorrespondence: Charles D Smith, Apogee Biotechnology Corporation, 1214 Research Blvd, Suite 2015, Hummelstown, PA, 17036, USA, Tel +1 843 814 9257, Email CDSmith@apogee-biotech.comAbstract: The Covid-19 pandemic driven by the SARS-CoV-2 virus continues to exert extensive humanitarian and economic stress across the world. Although antivirals active against mild disease have been identified recently, new drugs to treat moderate and severe Covid-19 patients are needed. Sphingolipids regulate key pathologic processes, including viral proliferation and pathologic host inflammation. Opaganib (aka ABC294640) is a first-in-class clinical drug targeting sphingolipid metabolism for the treatment of cancer and inflammatory diseases. Recent work demonstrates that opaganib also has antiviral activity against several viruses including SARS-CoV-2. A recently completed multinational Phase 2/3 clinical trial of opaganib in patients hospitalized with Covid-19 demonstrated that opaganib can be safely administered to these patients, and more importantly, resulted in a 62% decrease in mortality in a large subpopulation of patients with moderately severe Covid-19. Furthermore, acceleration of the clearance of the virus was observed in opaganib-treated patients. Understanding the biochemical mechanism for the anti-SARS-CoV-2 activity of opaganib is essential for optimizing Covid-19 treatment protocols. Opaganib inhibits three key enzymes in sphingolipid metabolism: sphingosine kinase-2 (SK2); dihydroceramide desaturase (DES1); and glucosylceramide synthase (GCS). Herein, we describe a tripartite model by which opaganib suppresses infection and replication of SARS-CoV-2 by inhibiting SK2, DES1 and GCS. The potential impact of modulation of sphingolipid signaling on multi-organ dysfunction in Covid-19 patients is also discussed.Keywords: opaganib, ABC294640, sphingolipid, sphingosine kinase, dihydroceramide desaturase, glucosylceramide synthase